2022
DOI: 10.1177/17562872221145625
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric ultrasound of prostate: role in prostate cancer diagnosis

Abstract: Recent advances in ultrasonography (US) technology established modalities, such as Doppler-US, HistoScanning, contrast-enhanced ultrasonography (CEUS), elastography, and micro-ultrasound. The early results of these US modalities have been promising, although there are limitations including the need for specialized equipment, inconsistent results, lack of standardizations, and external validation. In this review, we identified studies evaluating multiparametric ultrasonography (mpUS), the combination of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 124 publications
(251 reference statements)
0
8
0
1
Order By: Relevance
“…The ideal approach to the diagnosis of PCa should be to detect significant disease by performing a limited number of targeted biopsy cores and improving the accuracy of standard TRUS by mpUS; clinical studies have shown that mpUS increases sensitivity by 13-59% in detecting PCa 19 , 20 . In the last years, TRUS has been enriched by the introduction of tridimensional and computerized images ( Fig.…”
Section: Multiparametric Ultrasoundmentioning
confidence: 99%
“…The ideal approach to the diagnosis of PCa should be to detect significant disease by performing a limited number of targeted biopsy cores and improving the accuracy of standard TRUS by mpUS; clinical studies have shown that mpUS increases sensitivity by 13-59% in detecting PCa 19 , 20 . In the last years, TRUS has been enriched by the introduction of tridimensional and computerized images ( Fig.…”
Section: Multiparametric Ultrasoundmentioning
confidence: 99%
“…Der Binnenkontrast zur Detektion von Tumorgewebe ist jedoch nicht ausreichend [38]. Verschiedene neuere Techniken wie der Super-Resolution Ultraschall, ultraschnelle Doppler-sonographische Verfahren, die Ultraschall-Elastographie sowie die KM-verstärkte Sonographie (CEUS) und das Histoscanning haben den Begriff des multiparametrischen Ultraschalls (mpUS) geprägt und die Sensitivität angehoben [39]. Eine randomsierte, kontrollierte Studie mit 306 Patienten konnte jedoch eine Überlegenheit der mpMRT zeigen [40].…”
Section: Prostatakarzinomunclassified
“…However, internal contrast is not sufficient for detecting tumor tissue [38]. Several recent techniques such as super-resolution ultrasound, ultrafast Doppler sonographic techniques, ultrasound elastography, KM-enhanced sonography (CEUS) and histoscanning have coined the term multiparametric ultrasound (mpUS) and raised the sensitivity [39]. However, a randomized controlled trial of 306 patients demonstrated superiority of mpMRI [40].…”
Section: Prostate Carcinomamentioning
confidence: 99%
“…Two relatively recent studies compared a multiparametric TRUS approach utilizing grayscale imaging, color Doppler imaging, shear wave elastography, and contrast-enhanced ultrasound to mpMRI and found that the two approaches had comparable detection rates of localized prostate cancer [23,24]. However, additional studies and meta-analyses have not found that this approach outperforms MRI in most cases, and more research is needed with standardized protocols to validate the results [25].…”
Section: Ultrasoundmentioning
confidence: 99%